1991
DOI: 10.1080/00103629109368452
|View full text |Cite
|
Sign up to set email alerts
|

Copper availability in two soils amended with eleven annual applications of copper‐enriched hog manure

Abstract: Relatively high amounts of Cu are found in manure of hogs (Sus scrofa domesticus) maintained on diets containing growth-stimulating levels of Cu. While disposal of Cu-enriched hog manure through repeated long-term application to agricultural land is commonly practiced, concern exists regarding Cu availability in these soils. Field studies were conducted on a Bertie fine sandy loam (Aquic Hapludults) and a Starr-Dyke clay loam (Fluventic DystochreptsTypic Rhodudults), located in the Coastal Plain and Piedmont r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This was more evident in soils amended with SL and compost, which are rich in CaCO 3 and basic cations, respectively (Zhu et al 1991). The establishment of a plant cover (CTRP) also changed soil pH and produced a similar change to that found following addition of LEO (Fig.…”
Section: Soil Phmentioning
confidence: 72%
“…This was more evident in soils amended with SL and compost, which are rich in CaCO 3 and basic cations, respectively (Zhu et al 1991). The establishment of a plant cover (CTRP) also changed soil pH and produced a similar change to that found following addition of LEO (Fig.…”
Section: Soil Phmentioning
confidence: 72%
“…Immobilization of metals by such amendments is achieved through adsorption, complexation, and redox reactions (Adriano et al, 2004)-organic matter makes strong complexes with heavy metals (Krogstad, 1983). The addition of organic amendments has often been shown to increase the CEC of soils (Marques et al, 2007a), increasing cation adsorption caused by the dissociation of H + from the functional groups in organic matter (Zhu et al, 1991). The presence of phosphates, Al compounds, and other inorganic minerals in some organic amendments is also believed to be responsible for the retention of metals (Adriano et al, 2004).…”
Section: Phytostabilization Of Heavy Metalsmentioning
confidence: 98%
“…Addition of organic amendments has often been shown to increase the CEC of soils, increasing cation adsorption caused by the dissociation of H + from the functional groups in organic matter (Zhu et al, 1991). Bolan et al (2003) observed that CEC per unit organic carbon was higher for soils than for biosolid, which was attributed to the difference in the nature of organic matter or to the significant contribution of negative charge by the mineral components in soils.…”
Section: Organic (Biosolids) Residuesmentioning
confidence: 98%